Analysis of Leadership Styles in Enhancing Member Engagement and Performance in Organizations - Shilfy Zehana Aqilah Sinaga; Alya Alfarisa; Muhammad Chainur Rizki (Journal of Global Islamic Economic Studies, 2024)
This research focuses on analyzing leadership styles in increasing the involvement and performance of organizational members. Human resources, as the main asset in an organization, play a crucial role in achieving goals. Organizational success is highly dependent on the implementation of an effective leadership style, especially in the context of government organizations facing the challenges of bureaucratic reform. This research uses qualitative methods with a literature study approach to explore the relationship between transformational and democratic leadership styles and employee involvement and performance. The research results show that a transformational leadership style, with an approach to inspiring vision, emotional involvement, individual development, and intellectual stimulation, plays a significant role in creating a harmonious and productive work environment. Meanwhile, a democratic leadership style, which emphasizes active participation in decision making and appreciation of employees, can increase motivation and performance. The combination of these two leadership styles is effective in creating inclusive and innovative organizations. However, research also finds challenges in implementing leadership styles, such as lack of coordination, less firm decision making, and low employee awareness of responsibilities. Therefore, an integrative leadership strategy is needed to overcome these obstacles. This research provides recommendations for improving leadership competencies through effective communication, regular evaluations, and the development of relevant training programs. These findings are expected to contribute to more effective leadership practices in various organizational contexts.